Initial establishment of a farmer-based expriment network in the Indo-Gangetic Plans (IGP) Region: Pilot project for on-farm participatory climate change adaptation and visualization - Mathur, P.N. (2010)
Four project sites, namely: Karnal, Haryana; Ludhiana, Punjab; Pusa, Bihar; and Varanasi, Uttar Pradesh, were identified and agreed upon. At each project site ten farmers were selected to carry out field experiments and to participate in project activities as per the agreed workplan. Ten wheat varieties were identified for this study based on their past performance, namely: HD 2329, PBW 343, DBW 17, WH 711, HUW 234, K9107, K307, UP 262, HD 2733 and KRL 19. Seeds of these ten varieties were procured by the Directorate of Wheat Research (DWR), India, and trial sets were dispatched to each project site for timely sowing. Sowing of the experimental varieties was completed by 20 November, 2010, using a line sowing method with a recommended package of practices. A uniform plot size of 3 m x 6 m with three replications was used at each site. Staff of CIAT, CCAF-CP visited New Delhi to discuss the progress of the project activities and also visited two of the project sites (i.e. Karnal and Ludhiana), where they were able to meet with a few farmers who agreed to participate in the project. The team was impressed with the response from the scientific staff, as well as that of the farmers.